2010
DOI: 10.1075/la.168
|View full text |Cite
|
Sign up to set email alerts
|

Sentential Form and Prosodic Structure of Catalan

Abstract: This monograph presents an experimental and theoretical inquiry into the role of sentential form and variation in the prosodic structure of Catalan. The empirical section examines intonational phrasing across sentence forms, including SVO structures with either nominal or sentential objects and structures involving clitic left- and right-dislocations. The results show variation in phrasing that depends on syntactic factors and non-syntactic factors such as topic-hood and prosodic binarity. The theoretical sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 0 publications
1
26
2
1
Order By: Relevance
“…The other contour type, rising TOP, 26 also does not speak against one single ι, because TOP and VM form a plateau, which 27 signals prosodic coherence between the two. This result apparently contrasts 28 Hungarian with languages that have been claimed to realize the topic as forming a 29 separate intonational phrase, with a closing ι--boundary following it (see e.g., Frascarelli 30 2000, Féry 2006, Feldhausen 2010). 27 31 Furthermore, the above consequences for phrasing also bear on the issue of the 32 position of the nuclear pitch accent in Hungarian.…”
contrasting
confidence: 48%
“…The other contour type, rising TOP, 26 also does not speak against one single ι, because TOP and VM form a plateau, which 27 signals prosodic coherence between the two. This result apparently contrasts 28 Hungarian with languages that have been claimed to realize the topic as forming a 29 separate intonational phrase, with a closing ι--boundary following it (see e.g., Frascarelli 30 2000, Féry 2006, Feldhausen 2010). 27 31 Furthermore, the above consequences for phrasing also bear on the issue of the 32 position of the nuclear pitch accent in Hungarian.…”
contrasting
confidence: 48%
“…The latter can be achieved under the influence of prosodic constraints such as StrongStart or EqualSisters, for instance. It contrasts with a previous formulation of Align-Topic proposed by Feldhausen (2010), as given in (45). This constraint was put forward to account for left-dislocated topics in Catalan, which tend to align with the right-ege of an ι (or intermediate phrase) to the left of the core ι.…”
contrasting
confidence: 44%
“…Note that prosodic integration of complement clauses (and non-extraposed adjunct clauses) does not seem to be restricted to English. The same is possible and even preferred in Turkish (Kan 2009), Swedish (Myrberg 2010(Myrberg , 2013, Catalan (Feldhausen 2010), Xhosa (Jokweni 1995) and Durban Zulu (Cheng & Downing 2007). In this paper, we will show that this is also the case in Hungarian and Bàsàá.…”
Section: (4)mentioning
confidence: 95%
“…They found that the two dominant boundary tones in statements (located at the end of the first prosodic constituent) were either the continuation rise or the sustained pitch. By contrast, intonational phrase-final edges were generally signaled by a low boundary tone (L%) and a wider inventory of boundary tone combinations (see also Feldhausen, 2010). Fig.…”
Section: Prosodic Labelingmentioning
confidence: 92%
“…Catalan speakers place a prominent stress (what we will call p-phrase prominence) and an accent on the last tonic syllable of a p-phrase, and speakers produce an F0 continuation rise at the right boundary of a p-phrase, i.e., an H-boundary tone (Frota et al, 2007;Feldhausen, 2010). The two graphs in Fig.…”
mentioning
confidence: 98%